Creativity in noise: Transforming urban elements into innovative music in POSUA - Niki Sampurna, Muhammad Raihan; Ruchimat, Ismet; Herdini, Heri (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
This article examines the influence of urbanization and industrialization on musical expression, with a focus on the role of urban noise as a creative element. The processes of urbanization and industrialization are frequently linked with an increase in noise levels, which is commonly regarded as a form of noise pollution. Nevertheless, this article underscores the potential for such noise to be transformed into a valuable aesthetic element within musical compositions. The research employs electro-acoustic theory and innovative techniques to transform noise into a novel musical element. The methods utilized include sound exploration and experimentation, evaluation, and composition employing both conventional and unconventional instruments. The techniques of sound manipulation are also employed in order to transform noise into an engaging musical experience. The outcome of this research is the musical work POSUA, which illustrates how urban noise can be transformed into a contemplative and creative musical experience, encouraging listeners to perceive noise from an original and innovative perspective. This article introduces a novel perspective on the potential of noise as a musical material and its role in fostering diversity within the contemporary music landscape.